Forssman Prevalence in a Portuguese Donor Population. (24th June 2020) - Mourato, C; Corpuz, A; Sousa, J; Martins, D; Pereira, C; Tomaz, J; Barreira, R; Rocha, C; Mendes, F
Abstract: Introduction Discovered in 1911 by Frederick Forssman, the Forssman (Fs) antigen (Ag) expression varies among species, being rarely present on human red blood cells (RBC). In 1987 three unrelated English families were identified with a phenotype designed Apae which was later classified as the 31st blood group: FORS. Since antibodies (Ab) anti-Fs has natural occurrence and the expression of the Ag occurs on the surface of the RBC, body fluids and organs, raises a potential role for this antigen in transfusion and transplantation implications. Objectives Our main goals were to evaluate the prevalence of anti-Fs Ab and clarify its impact in transfusional medicine by classifying the type of immunoglobulin (Ig) involved. Methodology 3-5% sheep RBC suspension with positive expression for Fs Ag was used to evaluate the presence of Ab anti-Fs in plasma samples from a Portuguese population of blood donor and classify the immunoglobulin involved. Standard tube technique was used in all the experiments. Results From a total of 11877 donors, 117 (0, 99%) showed weak reactions (between 0 and 1 in a scale from 0 to 4). All these samples would be further studied to evaluate the presence of the Arg296Gln in the GBGT1 gene. Also, from the 192 samples studied to classify the Ab involved, 52% revealed to be only IgM, being the rest a mixture between IgG and IgM. Conclusion The population studied revealed few samples with negative reaction against the sheep RBC confirm the low-prevalence of this blood group. The majority from the Ab to be IgM was also corroborated although the presence of an IgG portion can be clinically significant once it can cross the placental barrier.